2018
DOI: 10.1093/jnci/djy097
|View full text |Cite|
|
Sign up to set email alerts
|

Systematic Identification of Druggable Epithelial–Stromal Crosstalk Signaling Networks in Ovarian Cancer

Abstract: Our findings suggest the feasibility of using novel multicellular systems biology modeling to identify and repurpose known drugs targeting cancer-stroma crosstalk networks, potentially leading to faster and more effective cures for cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 41 publications
0
42
0
Order By: Relevance
“…Another key component of the cancer microenvironment are cancer associated fibroblasts (CAFs). Yeung et al examined the gene expression profile of microdissected ovarian cancer cells and CAFs derived from HGSOC tumors [37]. They observed that cancer cells overexpress TGF-β, while CAFs can respond through activated Smad signaling.…”
Section: The Role Of Fibronectin In Ovarian Cancermentioning
confidence: 99%
“…Another key component of the cancer microenvironment are cancer associated fibroblasts (CAFs). Yeung et al examined the gene expression profile of microdissected ovarian cancer cells and CAFs derived from HGSOC tumors [37]. They observed that cancer cells overexpress TGF-β, while CAFs can respond through activated Smad signaling.…”
Section: The Role Of Fibronectin In Ovarian Cancermentioning
confidence: 99%
“…The tumor epithelium and surrounding microenvironment closely interact through the extracellular matrix or secreted factors such as exosomes, cytokines, and angiogenic factors (2). The depiction of a transcriptome map of the altered biological processes in the epithelial and stromal compartments will not only allow investigators to comprehensively understand the mechanism of cancer initiation and the complex coevolving relationships between the intrinsic and extrinsic factors of tumors (3) but also help in the detection of druggable epithelial-stromal crosstalk targets (4). Nishida previously used a laser capture microdissection (LCM)-processed miRNA and gene expression microarray to reveal two miRNA clusters with high expression in the cancer stroma (5).…”
Section: Introductionmentioning
confidence: 99%
“…LRRC32 is a key regulator of TGF-β activation 52 . Together with increased TGFB1 secreted by CD73_1 and CD73_2 CAFs, LRRC32 may generate an immune-suppressive and pro-tumorigenic microenvironment to support the malignant phenotype of ovarian cancer cells, as we previously described 53,54 . Both FN1 and TNC encode extracellular proteins that have previously been shown to be associated with short progression-free survival and increased migration-inducing potential in HGSC 55,56 .…”
Section: Correlations Between Cell Subtype Density and Transcriptomicmentioning
confidence: 62%
“…Extensive details of specimen handling, RNA extraction and ampli cation, microarray hybridization, and quality-control procedures have been described previously 54 .…”
Section: Microdissection and Microarray Analysis Of Tissue Samplesmentioning
confidence: 99%